A study among pulmonary tuberculosis patients under the treatment of directly observed treatment short course with special reference to liver function in tertiary care hospital - Paranthakan, C.; Govindarajan, P. K. (International Journal of Advances in Medicine, 2017)
Background: Directly observed treatment short course is the most effective life saving measure among the patients suffering from tuberculosis. Drug induced hepatotoxicity is one of the major side of anti-tuberculosis drugs which causes to withdraw the drugs. The objective of the study was to find out certain variables like age, sex and BMI among the patients with pulmonary tuberculosis and to find out liver function after intake of anituberculosis drugs. Methods: The patients diagnosed first time with pulmonary tuberculosis by sputum positive attending RNTCP DOTS Cell at tertiary care hospital were selected for this study.95 patients enrolled in this study during six months period and they were followed another six months to find out the status of liver function. BMI was measured, the investigation like serum albumin, liver function (aspartate aminotransferase (AST), alanine aminotransferase (ALT) alkaline phosphatase level test (ALP), serum bilirubin) were assessed at the time of initiation of anti-tuberculosis drugs and 2 weeks, 4 weeks and 24 weeks after the drugs. Chi-square test applied as a statistical tool. Results: Among study population of 95, 54% were male and 46% were female. Nearly 62% of the patients were in the age group of 18 to 48. Around 57% of the patients were underweight according to BMI. The liver function test was abnormal after drugs in 5.2% of the study population. Conclusions: This study shows that the tuberculosis affects the productive life of the population. The drugs given under DOTS did not harm majority of the patients that shows it is safe to administer the regime.